A Comprehensive Review of TORCH Syndrome: Characterization and Prevention Strategies - Konopka, Agata; Szczepaniak, Zuzanna; Wdowiak, Natalia; Lissak, Karina; Komarów, Małgorzata; Choinka, Martyna; Karasińska, Dominika; Kalisiak, Jakub (Quality in Sport, 2024)
Abstract: Introduction: TORCH syndrome refers to a group of symptoms caused by congenital infections with teratogenic pathogens, including Toxoplasma gondii, Varicella, Treponema pallidum, Parvovirus B19, Rubella, Cytomegalovirus (CMV), and Herpes simplex virus (HSV). It can also encompass infections like HIV, Zika virus (ZIKV), hepatitis B, and SARS-CoV-2. These pathogens can pass through the placenta, overcoming various placental barriers. Infections during pregnancy can result in severe consequences for both the fetus and the mother. Common symptoms in newborns include low birth weight, rashes, hepatosplenomegaly, cardiac anomalies, jaundice, chorioretinitis, and microcephaly, with 2% to 3% of congenital anomalies attributed to perinatal infections. The incidence of these infections varies globally. Purpose of the work: This study aims to review and characterize TORCH syndrome and the prevention of TORCH infections. Materials and methods: A comprehensive analysis of research papers available on PubMed, Google Scholar, Web of Science, Embase and Scopus was undertaken using the searchterms encompassing the following keywords: TORCH syndrome / infections during pregnancy / perinatal infections / Toxoplasmosis / Rubella / CMV infection / Herpes Simplex Virus infection / Parvovirus B19 / Treponema pallidum / vaccinations before and during pregnancy / maternal nutrition. Results: TORCH syndrome is a significant issue causing congenital diseases, premature births, and intrauterine deaths, impacting babies throughout their lives. Most complications can be prevented with proper prophylaxis and early treatment. Increasing awareness and providing education for women from preconception through the early postnatal period is essential. Addressing TORCH syndrome remains a major medical challenge, but improving management offers hope for better outcomes.